Urticaria- bane or boon to treat with omalizumab? A case series - Nagarajan, Sowmya Arudi; NS, Harsha; Sharma, Nagashree V (Indian Journal of Case Reports, 2019)
Chronic spontaneous urticaria (CSU) is a condition characterised by the presence of hives with/without angioedema that affects individuals on more days than not for 6 weeks or more. This can be a very debilitating condition affecting the quality of life. Here, we report 3 cases of severe prolonged chronic spontaneous urticaria in 7-year-old, 20-year-old and 25-year-old individuals that went into rapid remission following the treatment with Omalizumab, anti-IgE monoclonal antibody.